A tractable experimental model for study of human and animal scabies. - Kate Mounsey; Mei-Fong Ho; Andrew Kelly; Charlene Willis; Cielo Pasay; David J Kemp; James S McCarthy; Katja Fischer (Public Library of Science (PLoS), 2010)
BACKGROUND: Scabies is a parasitic skin infestation caused by the burrowing mite Sarcoptes scabiei. It is common worldwide and spreads rapidly under crowded conditions, such as those found in socially disadvantaged communities of Indigenous populations and in developing countries. Pruritic scabies lesions facilitate opportunistic bacterial infections, particularly Group A streptococci. Streptococcal infections cause significant sequelae and the increased community streptococcal burden has led to extreme levels of acute rheumatic fever and rheumatic heart disease in Australia's Indigenous communities. In addition, emerging resistance to currently available therapeutics emphasizes the need to identify potential targets for novel chemotherapeutic and/or immunological intervention. Scabies research has been severely limited by the availability of parasites, and scabies remains a truly neglected infectious disease. We report development of a tractable model for scabies in the pig, Sus domestica. METHODOLOGY/PRINCIPAL FINDINGS: Over five years and involving ten independent cohorts, we have developed a protocol for continuous passage of Sarcoptes scabiei var. suis. To increase intensity and duration of infestation without generating animal welfare issues we have optimised an immunosuppression regimen utilising daily oral treatment with 0.2 mg/kg dexamethasone. Only mild, controlled side effects are observed, and mange infection can be maintained indefinitely providing large mite numbers (> 6000 mites/g skin) for molecular-based research on scabies. In pilot experiments we explore whether any adaptation of the mite population is reflected in genetic changes. Phylogenetic analysis was performed comparing sets of genetic data obtained from pig mites collected from naturally infected pigs with data from pig mites collected from the most recent cohort. CONCLUSIONS/SIGNIFICANCE: A reliable pig/scabies animal model will facilitate in vivo studies on host immune responses to scabies including the relations to the associated bacterial pathogenesis and more detailed studies of molecular evolution and host adaptation. It is a most needed tool for the further investigation of this important and widespread parasitic disease.